Modification of Teri Fish Snack Bar with Moringa Leaf Addition to Increase Weight in Malnourished Toddlers - Frisilia, Jenita; Nirwan, Multy; Andhyka, Andhyka (Jurnal Ilmu Kesehatan, 2025)
The issue of wasting remains a major concern, with Indonesia being the second-highest country in the world for child wasting, reporting more than 760,000 cases of malnourished children. This figure poses a serious threat to the future of Indonesia's younger generation. The 2022 Indonesian Nutritional Status Survey (SSGI) shows that Sigi Regency ranks first in Central Sulawesi with the highest undernutrition rate (156%). Numerous toddler food products now include moringa leaves, and the government has addressed undernutrition through programs such as the Supplementary Feeding Program. Moringa leaves have been widely used to tackle malnutrition issues, as applied in Sigi Regency, where moringa and anchovy (Teri) are staple foods of the Kaili tribe. Local food modification efforts are among the strategies to enhance nutritional intake. This study aims to evaluate the effectiveness of modifying a snack bar made from anchovy fish and moringa leaves to improve weight in malnourished toddlers. The method used was a quasi-experimental design with 40 undernourished toddlers whose weights were measured before and after consuming the modified snack bar. Results showed a significant improvement in the nutritional status of the toddlers, especially for those previously classified as severely malnourished.